Dermoids of the Maxillofacial Region: A study on clinical presentation and surgical management - Divashree Sharma; Geeta Mishra Tripathi; Ambrish Mishra; Neelam Shakya (Wolters Kluwer Medknow Publications, 2022)
Introduction: Dermoid and epidermoid cysts commonly termed as "Dermoids" are known to be developmental benign swellings that possibly occur as a result of traumatic implantation of epithelium or entrapment of epithelial remnants during embryonic fusion. The occurrence is rare (about 7%) in the head-and-neck region and they represent <1.6% of all cysts of the oral cavity. Patients and Methods: A retrospective study was done on 12 histopathologically proven cases of epidermoid and dermoid cysts of the maxillofacial region that were treated in Shyam Shah Medical College, Rewa, Madhya Pradesh, India, from January 2013 to December 2019. The cases were evaluated for clinical presentation, demographic characteristics, and treatment performed. Results: Out of a total of 12 cases that were included in this study, 10 cases were diagnosed as epidermoid and 2 cases as true dermoid cysts. The mean age of occurrence was 31.66 ± 9.97 years. Male predominance was seen with a male-to-female ratio of 1.4:1. The floor of the mouth was the most commonly involved site in ten (83.34%) cases. Sublingual cysts were seen in five (41.67%) cases, combined sublingual-submandibular involvement in three (25%) cases, and midline floor of the mouth cyst in two (16.67%) cases. All the cases were treated by surgical enucleation, and no recurrence or malignant transformation was reported in any case at a minimum follow-up of 2 years. Conclusion: Based on the findings of this retrospective study, it is suggested that these lesions are very rare in the maxillofacial region and pose a diagnostic challenge. However, fine-needle aspiration cytology, ultrasound imaging, computerized tomography, and magnetic resonance imaging techniques can be relied upon for precise treatment planning. Surgical enucleation of these lesions is the preferred treatment modality.